EXPERT INTERVIEW ANALYSIS WITHIN THE STATE EMPLOYMENT AGENCY’S MEASURE “MOTIVATION PROGRAM FOR JOB SEEKING AND SOCIAL MENTOR SERVICES” - Zahare, Astrīda (Education Reform: Education Content Research and Implementation Problems, 2019)
Currently long-term unemployment is a significant problem in Latvian labour market, therefore a topical issue is the integration of the long-term unemployed into the labour market, as well as low motivation of the target population.From December 2015 till 31 December 2021 an ESF project “Support for the Long-term Unemployed” is being implemented, this project includes the implementation of a measure “Motivation Program for Job Seeking and Social Mentor Services” which aims to motivate and to preventively support the long-term unemployed, as well as to facilitate their placement in appropriate permanent workplaces.Aim of the expert interviews was to find out whether the motivation of the long-term unemployed was changed during the State Employment Agency’s measure “Motivation Program for Job Seeking and Social Mentor Services”, and in case of affirmative result to observe what were these changes. In addition, the data from expert interviews were compared with the data from the questionnaires that were completed by the participants in the measure.